Financial Management Accountability Index (FMAI) in the Malaysian public sector: a way forward - Abu Bakar, Nur Barizah; Ismail, Suhaiza (SAGE journals online, 2011)
The National Audit Department (NAD) of Malaysia has introduced the Financial Management Accountability Index (FMAI) within the framework of the audit rating system. This study shares the Malaysian experience in using FMAI as an accountability medium, evaluates the FMAI scores obtained by agencies, and proposes measures to enhance the usefulness of FMAI. The study uses secondary data as provided on the NAD website. Descriptive analyses were conducted in evaluating the rating scores across agencies. It was found that majority of the agencies have a ‘good’ financial management system, with Federal agencies performing better than their counterparts at the State level. It was also found that the overall rating system and FMAI suffer from lack of proper disclosure, consequently reducing their worthiness. There are still areas of improvement that need to be addressed by the NAD to enhance the value of the overall audit rating system.